PROBLEMS OF BIODIVERSITY AND MEASURES FOR ITS CONSERVATION - Urinova , Adolat Abdivasievna; Sobirov , Faridun Shavkatovich (Educational Research in Universal Sciences, 2024)
Not only in the world, but also in our country, existing species in nature are decreasing. To date, the processes of biodiversity reduction have reached record levels. The level of productivity in our lands is sharply decreasing. More than a million species of flora and fauna around the world are at risk of extinction. Humanity is faced with new biological threats. The article provides information about the attention to biodiversity conservation in Uzbekistan and the biodiversity conservation measures implemented today.